Urinary Mercury Levels Among Workers in E-waste Shops in Nakhon Si Thammarat Province, Thailand - Somsiri Decharat (Korean Society for Preventive Medicine, 2018)
Objectives To determine urinary mercury levels in e-waste workers in Southern Thailand and the airborne mercury levels in the e-waste shops where they worked, to describe the associations between urinary and airborne mercury levels, and to evaluate the prevalence of mercury exposure-related health effects among e-waste workers. Methods A cross-sectional study was conducted by interviewing 79 workers in 25 e-waste shops who lived in Nakhon Si Thammarat Province, Thailand. Information on general and occupational characteristics, personal protective equipment use, and personal hygiene was collected by questionnaire. Urine samples were collected to determine mercury levels using a cold-vapor atomic absorption spectrometer mercury analyzer. Results The e-waste workers' urinary mercury levels were 11.60±5.23 μg/g creatinine (range, 2.00 to 26.00 μg/g creatinine) and the mean airborne mercury levels were 17.00±0.50 μg/m3 (range, 3.00 to 29.00 μg/m3). The urinary and airborne mercury levels were significantly correlated (r=0.552, p<0.001). The prevalence of self-reported symptoms was 46.8% for insomnia, 36.7% for muscle atrophy, 24.1% for weakness, and 20.3% for headaches. Conclusions Personal hygiene was found to be an important protective factor, and should therefore be stressed in educational programs. Employers should implement engineering measures to reduce urinary mercury levels and the prevalence of associated health symptoms among e-waste workers.